Pictures that tick short narrative - McKean, Dave 1963- (Dark Horse Comics, 2014)
McKean uses mixed media to take readers on a journey unlike any other: "The Coast Road" follows a desperate wife trying to find her missing husband, whose ghostly image appears in unexpected ways. "Black Holes," written by an anonymous journalist, concerns the politically sensitive true story of Chinese villagers induced by the government to sell their blood, only to be infected with AIDS through poor medical practice. Tales of sadness and humor, insightful travelogues, and diary entries fill the pages of McKean's latest masterful achievement. Winner of the Victoria and Albert Museum Illustrated Book of the Year award
Featuring "The coast road", "The rut", "Blue tree", and "Black Holes"
Keywords: Graphic novels; Comic